A citation based ranking of German-speaking researchers in business administration with data of Google Scholar - Alexander Dilger; Harry Müller (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2010)
The quantitative evaluation of research performance in business administration has recently gained some attention in German-speaking countries. This holds especially for rankings of persons, which are discussed controversially. Rankings of academics can be constructed in two different ways, either based on journal rankings or based on citations. Despite citation based rankings promise some fundamental advantages, they are still not common in German-speaking business administration. However, the choice of the underlying data base is crucial. This paper argues that for German-speaking researchers in business administration (as an example for a non-English speaking scientific community in the social sciences) Google Scholar is an appropriate data base. Unfortunately, it contains some structural errors that require diligent corrections. With that in mind, all 1,572 members of the German Academic Association for Business Research (VHB, membership data by 2007) are ranked according to the citations of their recent publications (2005-2009). Obviously the citations follow a Pareto distribution amongst the scholars with large rank differences only at the top. The results are compared to those of the Handelsblatt-BWL-Ranking which is the most prominent journal based ranking of German-speaking academics in this discipline. It becomes clear that differences in method lead to different results. – – Die Messung von Forschungsleistungen mittels quantitativer Indikatoren hat in der deutschsprachigen Betriebswirtschaftslehre an Bedeutung gewonnen. Im Fokus des Interesses wie auch der Kritik stehen insbesondere Personenrankings, für deren Erstellung zwei Ansätze zur Verfügung stehen, entweder aufbauend auf einem Zeitschriftenranking oder direkt auf die individuellen Zitationen bezogen. Obwohl zitationsbasierte Personenrankings konzeptionelle Vorteile gegenüber zeitschriftenbasierten Rankings aufweisen, sind sie in der deutschsprachigen Betriebswirtschaftslehre bislang eher ungebräuchlich. Dabei kommt der verwendeten Datengrundlage eine entscheidende Bedeutung zu. In diesem Beitrag wird argumentiert, dass für die deutschsprachige BWL (als Beispiel für eine nicht genuin englischsprachige Sozialwissenschaft) Google Scholar eine geeignete Grundlage bilden kann. Angesichts einiger struktureller Fehler in Google Scholar erfordert die Erstellung eines Rankings allerdings eine sorgfältige Durchsicht und Nachkorrektur des Datensatzes. Auf diese Weise wurden die insgesamt 1.572 Mitglieder des Verbands der Hochschullehrer für Betriebswirtschaft (VHB, Mitgliederverzeichnis 2007) entsprechend der Zitationen ihrer aktuellen Veröffentlichungen (2005-2009) gerankt. Dabei fällt auf, dass die Zitationen höchst ungleich verteilt sind und einer Pareto-Verteilung entsprechen. Die Ergebnisse werden mit denen des Handelsblatt-BWL-Rankings verglichen, wobei deutlich wird, dass methodische Unterschiede auch zu anderen Resultaten führen.
Keywords: I23; I20; A11; C81; I29; M00; 330